2018
DOI: 10.1016/j.amsu.2018.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Malignant phyllodes tumor with metastases to lung, adrenal and brain: A rare case report

Abstract: BackgroundPhyllodes tumors are spectrum of tumors ranging from benign to malignant. Malignant spectrum pose a management challenge for clinicians due to high risks of recurrence and metastasis. Malignant phyllodes tumor with brain, lung and adrenal metastases at the same time is rare.Case presentationA 37 years-old unmarried female presented with an ulcerated huge lump in left breast with severe bleeding. Trucut biopsy showed necrosis with spindle cell proliferation with atypia for which she underwent modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In our study, the most common histotypes were in agreement with the previous results. Furthermore, we also found some cases of rare sarcoma subtypes, including glomus tumor, endometrial stromal sarcoma and phyllodes tumor, for which there are case reports of brain metastases [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most common histotypes were in agreement with the previous results. Furthermore, we also found some cases of rare sarcoma subtypes, including glomus tumor, endometrial stromal sarcoma and phyllodes tumor, for which there are case reports of brain metastases [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine effective therapeutic plans for PTs, distinguishing between benign, borderline, and malignant is crucial in that there is significant variability in the interpretation of the criteria for each designation [16]. For diagnosing precisely in cases with malignant PTs, chest and abdomen should be screened with contrast enhanced CT at least even if the patient is asymptomatic [4].…”
Section: Discussionmentioning
confidence: 99%
“…The median size of PTs is about 4 cm. Those size larger than 10 cm are less than 10% of PTs, and the largest one so far is up to 50 × 50 cm reported by Islam et al [ 4 , 5 ] Approximately 10–15% of PTs are malignant, and only 10–26% of malignant PTs are found with metastasis [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Koh et al [26] showed that a combination of large tumor size (≥90 mm) ant the presence of malignant heterologous elements had a statistically significant association with the development of distant metastasis. Most frequently, malignant PTs metastasize to the lung, bones, brain, and liver [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Few rare distant metastatic sites are the adrenal glands [20] , kidney [13] , skin [27] , ovary [28] , heart [29] , pleura [30] , oral cavity [31] , duodenum [32] , pancreas [33] , tonsillar [12] , and para-aortic nodes [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reports that 10%-15% of PTs are malignant and approximately 9%-27% of patients with malignant phyllodes tumor have metastasis to distant organs with spreading hematogenously to most frequent sites as lungs, bones, brain, and liver [6] . Recurrence or metastasis of breast PTs predicts a shorter survival time, less than 2 years after diagnosis [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%